Passivated graphene transistors fabricated on a millimeter-sized single-crystal graphene film prepared with chemical vapor deposition. (30th June 2015) - Lin, Meng-Yu; Wang, Cheng-Hung; Chang, Shu-Wei; Lee, Si-Chen; Lin, Shih-Yen
Abstract: In this work, we first investigate the effects of partial pressures and flow rates of precursors on the single-crystal graphene growth using chemical vapor depositions on copper foils. These factors are shown to be critical to the growth rate, seeding density and size of graphene single crystals. The prepared graphene films in millimeter sizes are then bubbling transferred to silicon-dioxide/silicon substrates for high-mobility graphene transistor fabrications. After high-temperature annealing and hexamethyldisilazane passivation, the water attachment is removed from the graphene channel. The elimination of uncontrolled doping and enhancement of carrier mobility accompanied by these procedures indicate that they are promising for fabrications of graphene transistors.